PERSEPSI KONSUMEN TERHADAP KUALITAS LAYANAN, VARIASI PRODUK DAN HARGA (STUDI PADA PASAR TRADISIONAL DAN MODERN DI KECAMATAN SEMARANG TIMUR) - Nawazirul Lubis, Sari Listyorini , (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The development of modern market more lively, a traditional market for stimuli to self first settled soon. The number of traditional markets is much less than the modern market, but its existence could not be denied again. This research aims to find out and analyze the differences between consumer perception of the modern market with traditional markets associated with the factor of price, product variety, and quality of service in the Eastern Town of Semarang.Based on the calculation of the mean, the modern market is higher than the traditional markets. According to the test result shows that paired t test perceptions of respondents about the quality of service is different between traditional and modern markets. Second, the respondent's perception of product variations is not different between traditional and modern markets. Third, the respondent about the price of a product is not different between traditional and modern markets.